2013
DOI: 10.1007/s13204-013-0251-8
|View full text |Cite
|
Sign up to set email alerts
|

Nano-Fe as feed additive improves the hematological and immunological parameters of fish, Labeo rohita H.

Abstract: An experiment was conducted to compare the effects of iron oxide nanoparticles (T 1 ) and ferrous sulfate (T 2 ) on Indian major carp, Labeo rohita H. There were significant differences (P \ 0.05) in the final weight of T 1 and T 2 compared with the control. Survival rates were not affected by the dietary treatments. Fish fed a basal diet (control) showed lower (P \ 0.05) iron content in muscle compared to T 1 and T 2 . Furthermore, the highest value (P \ 0.05) of iron content was observed in T 1 . In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 38 publications
4
28
0
Order By: Relevance
“…This may be attributed to the ease with which Fe nano be taken up by body and higher absorption and avilability on the contrary conventional Fe as mentation by Feng et al, (2009). Also this was agree with Behera et al (2014) who cleared that, nano-Fe appeared to be more effective than ferrous sulfate in increasing muscle iron and hemoglobin content. On the other hand, fish fed bulk Fe and Zn, their livers and gills contained Fe concentrates more than those fed Fe and Zn in nanoparticles.…”
Section: Accumulation Of Fe and Zn In Tissuessupporting
confidence: 73%
“…This may be attributed to the ease with which Fe nano be taken up by body and higher absorption and avilability on the contrary conventional Fe as mentation by Feng et al, (2009). Also this was agree with Behera et al (2014) who cleared that, nano-Fe appeared to be more effective than ferrous sulfate in increasing muscle iron and hemoglobin content. On the other hand, fish fed bulk Fe and Zn, their livers and gills contained Fe concentrates more than those fed Fe and Zn in nanoparticles.…”
Section: Accumulation Of Fe and Zn In Tissuessupporting
confidence: 73%
“…7 Moreover, Behera et al have recently demonstrated that FeNPs supplemented in the basal diet could improve the nal weight of treated sh. 6 In another study, Muralisankar and his co-workers observed improved performance in the survival, growth and activities of fresh water prawn sh treated with a ZnNP supplementary diet. 4…”
Section: Water Quality and Growth Performance Studymentioning
confidence: 96%
“…Nanotechnology has been growing explosively worldwide and become a ubiquitous tool for solving various aquaculture problems, including sh nutrition, 6 water quality management, and disease treatment. During the past few years, various engineered nanoparticles [NPs] have been reported for micronutrient delivery, such as FeNPs, 6 ZnNPs, 4 SeNPs, [7][8][9] AgNPs, 10 MnNPs, 11 CuNPs 12 etc. Iron (Fe) is an essential micronutrient for the functioning of tissues and organs of animals, including sh.…”
Section: Introductionmentioning
confidence: 99%
“…To date, metallic nanoparticles are mostly prepared from noble metals, i.e. silver (Vankar and Shukla 2012), gold (Dash et al 2014), copper, zinc and titanium (Schabes-Retchkiman et al 2006) as well from cadmium (Suresh 2014), iron (Behera et al 2013) and alginate (Asadi 2014). Among the noble metals, silver (Ag) is the metal of choice in the field of biological system, living organisms and medicine (Parashar et al 2009).…”
Section: Introductionmentioning
confidence: 99%